From 1D to 2D: dopamine constructed 2D NiCo-hydroxide nanosheets/graphene composites for high-performance supercapacitors. Issue 8 (6th April 2021) - Zhang, Xu; Yang, Shixuan; Tian, Yuhan; Liu, Anmin; Lu, Wang; Qu, Ning; Guo, Minggang; Mi, Panpan
Abstract : 2D NiCo-hydroxide nanosheets/graphene@PDA composites have been successfully fabricated by a dopamine-based construction strategy. The as-obtained positive electrode exhibits high specific capacitance and excellent rate capability. Abstract : A dopamine (DA)-based construction strategy is reported for designing high performance 2D NiCo-hydroxide nanosheets/graphene@polydopamine (NiCo-OH/G@PDA) composites. The strong coordination bond energies between the dopamine and metal ions are crucial for PDA to induce the formation of NiCo-OH nanosheets. The 2D structured NiCo-OH nanosheets can shorten the transportation path of charge and electrons and provide abundant redox reaction sites to enhance the pseudocapacitance. The high redox activity of N/O groups of PDA can also boost the pseudocapacitance to enhance the electrochemical performance. Moreover, the existing graphene in the NiCo-OH/G@PDA composite may construct a conductive network to boost redox reactions. Owing to the synergic effects of 2D NiCo-OH nanosheets, PDA and graphene, the prepared NiCo-OH/G@PDA with an optimized amount of DA delivers a high capacity of 1520 F g −1 at 1 A g −1 with an excellent rate capability of 68% at 50 A g −1 and good cycling stability. Furthermore, the assembled asymmetric supercapacitor exhibits a high energy density of 47 W h kg −1 at a power density of 1600 W kg −1 . This work can provide a promising novel strategy for the development of 2D metal hydroxides for high-performance supercapacitors.